Comparison between BS 5950: part 1: 2000 & Eurocode 3 for the design of multi-storey braced steel frame - Chan, Chee Han (2006)
Reference to standard code is essential in the structural design of steel structures. The contents of the standard code generally cover comprehensive details of a design. These details include the basis and concept of design, specifications to be followed, design methods, safety factors, loading values and etc. The Steel Construction Institute (SCI) claimed that a steel structural design by using Eurocode 3 is 6 – 8% more cost-saving than using BS 5950: Part 1: 2000. This study intends to testify the claim. This paper presents comparisons of findings on a series of two-bay, four-storey braced steel frames with spans of 6m and 9m and with steel grade S275 (Fe 460) and S355 (Fe 510) by designed using BS 5950: Part 1: 2000 and Eurocode 3. Design worksheets are created for the design of structural beam and column. The design method by Eurocode 3 has reduced beam shear capacity by up to 4.06% and moment capacity by up to 6.43%. Meanwhile, structural column designed by Eurocode 3 has compression capacity of between 5.27% and 9.34% less than BS 5950: Part 1:2000 design. Eurocode 3 also reduced the deflection value due to unfactored imposed load of up to 3.63% in comparison with BS 5950: Part 1: 2000. However, serviceability limit states check governs the design of Eurocode 3 as permanent loads have to be considered in deflection check. Therefore, Eurocode 3 produced braced steel frames which consume 1.60% to 17.96% more steel weight than the ones designed with BS 5950: Part 1: 2000. However, with the application of partial strength connections, the percentage of difference had been reduced to the range of 0.11% to 10.95%.